Greening TVET for Sustainable Skill Development: Opportunities and Challenges in Botswana with a Focus on Quality Education - Jerald, Hondonga; Tawanda, Chinengundu; Vijayaratnam , Phawani; Rajanthran , Subashini K (Journal of Ecohumanism, 2024)
The need to reorganise economies and the skill sets that individuals will need in the new order is urgent since climate change is impacting the entire planet. TVET systems are required to reskill and provide human capital with environmentally sustainable skills for green economies and jobs. This article investigates potential additional benefits that greening TVET education may offer to students, the employment market, and Botswana as a whole. The study examined current research on Botswana’s preparedness for a green TVET industry. Results highlight the crucial role of greening TVET systems in supporting nations to achieve the Sustainable Development Goals (SDGs), particularly in meeting their climate change commitments and ensuring quality education. Investments made concurrently in greening TVET, green industries, and green technology have the potential to prevent significant employment losses and to create a significant number of new jobs for recent graduates. The emphasis should be on occupational green skills and any support mechanisms that may establish a green TVET system to take advantage of the new prospects. Additional findings point to the need for strong labour market data and skills anticipation to pinpoint in-demand green talents and create fresh initiatives focused on the green economy. To lessen potential issues of fragmentation between TVET greening programmes, environmental legislation, and the green job market, countries must have professionals to perform quality assurance and monitoring of the novel synergies between the greening of TVET systems, learner skills, and the job market.